Sleep quality and associated factors among nurses working at comprehensive specialized hospitals in Northwest, Ethiopia - Segon, Tesfaye; Kerebih, Habtamu; Gashawu, Fanuel; Tesfaye, Bizuneh; Nakie, Girum; Anbesaw, Tamrat (Frontiers in Psychiatry, 2022)
Abstract Background: Poor sleep quality is common among nurses. This problem possibly results in negative emotional and psychological consequences in nurses which secondary affect their work performances. However, in Ethiopia, there is a paucity of information about poor sleep quality and associated factors among nurses. This study aimed to assess the prevalence of poor sleep quality and associated factors among nurses working at comprehensive specialized hospitals in Northwest Ethiopia. Methods: An institutional-based cross-sectional study was conducted among 542 nurses who worked at University of Gondar (UOG), Tibebe Ghion, Felege Hiwot Comprehensive Specialized Hospitals, Ethiopia, who were incorporated into the study through a simple random sampling technique from May 1 to June 2, 2021. The Pittsburgh sleep quality index (PSQI) with a cut score of above 5 was used to assess sleep quality using a structured self-administered questionnaire. Other tools used are Depression Anxiety Stress Scales (DASS-21), Shift Work sleep disorders (SWSD), and Oslo -3 social support scales. Epi-Data version 3.1 was used for data entry and SPSS version 25 was used for data analysis. A multivariable logistic regression analysis was performed to identify variables that have a significant association with poor sleep quality among nurse professionals. The degree of association was assessed using an odds ratio (OR) with a 95% confidence interval (CI) at a two-tailed p-value of < 0.05. Results: A total of 510 nurses were included in the study with a response rate of 94%. The study showed that the overall prevalence of poor sleep quality among nurses was 75.5% (95% CI (71.8, 79.1). Being female (AOR=1.72:95% CI =1.19, 2.28), depressive symptoms (AOR=2.24:95% CI=1.24, 3.85), anxiety symptoms (AOR=2.12: 95% CI =1.23, 3.62), stress (AOR = 2.85: 95% CI=1.67, 4.82) and current alcohol drinking (AOR=1.84 :95% CI=1.27, 3.13) were significantly associated with poor sleep quality. Conclusions: The overall prevalence of poor sleep quality among nurses was high. Being female, depressive symptoms, anxiety symptoms, stress, and current alcohol drinking had been significantly associated with poor sleep quality. Therefore, it is essential to institute effective intervention strategies emphasizing contributing factors to poor sleep quality.